Chemopreventive activity of methanol extract of Melastoma malabathricum leaves in DMBA-induced mouse skin carcinogenesis - Ooi, Samuel Kah Kooi; Cheah, Yee Ling; Rodzi, Roihanah; Othman, Fezah; Mohtaruddin, Nurhafizah; Suhaili, Zarizal; Zakaria, Zainul Amiruddin (African Traditional, Herbal Medicine Supporters Initiative, 2014)
Background: Melastoma malabathricum L. Smith (family Melastomaceae) is a shrub that has been used by the Malay practitioners of traditional medicine to treat various types of ailments. The present study aimed to determine the chemopreventive activity of methanol extract of M. malabathricum leaves (MEMM) using the standard 7,12-dimethylbenz(α)anthracene (DMBA)/croton oil-induced mouse skin carcinogenesis model. Materials and Methods: In the initiation phase, the mice received a single dose of 100µl/100 µg DMBA (group I-V) or 100µl acetone (group VI) topically on the dorsal shaved skin area followed by the promotion phase involving treatment with the respective test solutions (100 μl of acetone, 10 mg/kg curcumin or MEMM (30, 100 and 300mg/kg)) for 30 min followed by the topical application of tumour promoter (100µl croton oil). Tumors were examined weekly and the experiment lasted for 15 weeks. Results: MEMM and curcumin significantly (p<0.05) reduced the tumour burden, tumour incidence and tumour volume, which were further supported by the histopathological findings. Conclusion: MEMM demonstrated chemoprevention possibly via its antioxidant and anti-inflammatory activities, and the action of flavonoids like quercitrin.